Critical Infrastructure Protection IV Fourth Annual IFIP WG 11.10 International Conference on Critical Infrastructure Protection, ICCIP 2010, Washington, DC, USA, March 15-17, 2010, Revised Selected Papers - Moore, Tyler.; Shenoi, Sujeet. (IFIP Advances in Information and Communication Technology,, 2010)
The information infrastructure---comprising computers, embedded devices, networks and software systems---is vital to day-to-day operations in every sector: information and telecommunications, banking and finance, energy, chemicals and hazardous materials, agriculture, food, water, public health, emergency services, transportation, postal and shipping, government and defense. Global business and industry, governments, indeed society itself, cannot function effectively if major components of the critical information infrastructure are degraded, disabled or destroyed. Critical Infrastructure Protection IV describes original research results and innovative applications in the interdisciplinary field of critical infrastructure protection. Also, it highlights the importance of weaving science, technology and policy in crafting sophisticated, yet practical, solutions that will help secure information, computer and network assets in the various critical infrastructure sectors. Areas of coverage include: Themes and Issues, Control Systems Security, Infrastructure Security, Infrastructure Modeling and Simulation, and Risk Management. This book is the fourth volume in the annual series produced by the International Federation for Information Processing (IFIP) Working Group 11.10 on Critical Infrastructure Protection, an international community of scientists, engineers, practitioners and policy makers dedicated to advancing research, development and implementation efforts focused on infrastructure protection. The book contains a selection of seventeen edited papers from the Fourth Annual IFIP WG 11.10 International Conference on Critical Infrastructure Protection, held at the National Defense University, Washington, DC, USA in the spring of 2010. Critical Infrastructure Protection IV is an important resource for researchers, faculty members and graduate students, as well as for policy makers, practitioners and other individuals with interests in homeland security. Tyler Moore is a Postdoctoral Fellow at the Center for Research on Computation and Society, Harvard University, Cambridge, Massachusetts, USA. Sujeet Shenoi is the F.P. Walter Professor of Computer Science at the University of Tulsa, Tulsa, Oklahoma, USA.